Weight reduction of a standard brake drum: A design approach - Rambabu, D.; Gopinath, R; Senthil rajan, U.; Bhaskar, G.B. (International Journal of Engineering and Technology, 2014)
A Brake drum is specialized brake that uses the concept of friction to decelerate the vehicle speed. The deceleration is achieved by the assistance of the friction generated by a set of brake shoes or pad, when operator presses against a rotating brake drum. The material generally preferred for making the brake drum is grey cast iron or vermicular cast iron. The drum brake is highly efficient for hand brake and service brake applications. During the operation of drum brake excessive heating of brake drum may occur. This excessive heating occurs due to repeated or frequent contact of the brake shoes against the drum. This causes the drum to crack, oversize, extreme wear, out of round drums and also leads to vibration which while braking will leads to reduced brake drum life and braking efficiency. The Un-laden weight of the vehicle will result in increased fuel consumption, reduced payload and ride handling characteristics. The objective of the paper is to improve the thermal characteristics by incorporating fins in the brake drum and to reduce the un-laden weight of the vehicle by changing the rib thickness, wall thickness and base flange thickness. The design is done by using 3D CAD Modelling software and Hexahedral finite element model prepared by using CAE pre-processing software and Stiffness analysis. Design iterations are carried out by using Linear/Non-linear Finite Element Solvers, Stress Displacement and Temperature is post-processed for design validation. Optimized design solution obtained based on the comparison study between the iteration with rib thickness 75 mm, star shaped removal and wall thickness 17 mm has been chosen. 1.8Kg of weight is being reduced from the brake drum including fins.   Keywords: Drum Brake, 3D CAD Modelling, Para Metric Matrix, Structural Analysis, Fins.